Distribution of Tuna (Thunnus sp.) Landed at Binuangeun Fish Landing Base of Banten Province - Anggara, Rega; Irnawati, Ririn; Hamzah, Asep (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Binuangeun Fish Landing Base (FLB) is the largest tuna-producing port in Banten Province. Tuna production in 2019 amounted to 26% of the total catch. The purpose of this study was to identify distribution activities and calculate marketing efficiency. The research was conducted in February-August 2023 at Binuangeun FLB of Banten Province. The method used is the survey method. The sampling technique was carried out by purposive sampling. Margin analysis and marketing efficiency (Fisherman's share) are used to determine differences in fish prices, as well as how efficient the marketing process is. The results obtained are four marketing channels, namely the first channel (fisherman, fish auction, fish brokers, consumers), the second channel (fisherman, fish auction, collectors, processing, companies, consumers), the third channel (fisherman, fish auction, collectors, traders outside the region, consumers), the fourth channel (fisherman, fish auction, fish brokers, retailers, consumers). The highest margin is found in marketing channel II, which is IDR 10,000 (50%). The lowest margin is found on the fourth channel with a value of IDR 3,000 (12%). Tuna marketing at PPI Binuangeun is quite efficient. The highest efficiency value is found in marketing channel one. The lowest efficiency value is found in the second channel.